A Literature Review on Mantra Meditation - Ravi Saini; Jitender Sorout (Medical and Health Science Journal, 2023)
Objective: Meditation has gained popularity in modern times as an adjunctive of therapeutic treatment. This study aimed to study meditation and use of mantra meditation in application of health problems.